Comparison of Outcomes of Laminoplasty and Laminectomy with Fusion and Internal Fixation in Patients with Cervical Spondylotic Myelopathy (CSM) - Fatima, Kinza; Ali, Muhammad Faiq; Zulqarnain, .; Shaukat, Shuja; Ali, Farhad; Shah, Irfan Ali (Biological and Clinical Sciences Research Journal, 2025)
Cervical spondylotic myelopathy (CSM) and ossification of the posterior longitudinal ligament (OPLL) are major causes of progressive spinal cord compression in adults. Surgical decompression is the standard treatment, with laminoplasty and laminectomy with fusion being two widely employed techniques. However, comparative evidence regarding functional outcomes and recovery patterns in these procedures remains limited, particularly in South Asian populations. Objective: To evaluate variations in patient outcomes and recovery between the two surgical techniques; to compare the efficacy of laminoplasty and laminectomy with fusion and internal fixation in the management of CSM and Cervical OPLL. Methods: The study was designed as a prospective, randomized controlled trial conducted in the Department of Neurosurgery at Civil Hospital Karachi over three months, from August 2024 to January 2025, following ethics approval of the study protocol. Adult patients aged 40 years or older presenting with multilevel cervical spondylotic myelopathy (including OPLL) who had failed conservative therapy and demonstrated two or more levels of spinal cord compression were screened for eligibility. Results: Peri- and postoperative pain, assessed using the Visual Analog Scale (Table 2), improved in both cohorts, although no statistical significance was observed between them at any time point. Preoperatively, Group A reported a mean VAS of 7.13 ± 1.09 versus 6.80 ± 0.90 in Group B (p = 0.144). At one-month post-op, scores fell to 5.20 ± 1.23 and 4.84 ± 1.15 (p = 0.059); at three months, to 4.24 ± 1.32 and 3.86 ± 1.31 (p = 0.139); and by six months, to 3.78 ± 1.40 and 3.33 ± 1.31 (p = 0.096). Functional status measured by the modified Japanese Orthopaedic Association score is detailed in Table 3. Baseline mJOA scores were 10.3 ± 1.88 in Group A and 10.6 ± 1.67 in Group B (p = 0.396). Both groups showed progressive neurological recovery: at one month, means rose to 12.3 ± 2.13 versus 12.8 ± 1.87 (p = 0.215); at three months, to 13.3 ± 2.10 versus 13.9 ± 1.90 (p = 0.137); and at six months, to 13.8 ± 2.06 versus 14.4 ± 2.00 (p = 0.119), again with no significant intergroup differences. Conclusion: Open-door laminoplasty and laminectomy with fusion provide equivalent midterm improvements in multilevel CSM, with laminoplasty offering shorter operative time.